Efek perlakuan awal dengan pulsed electrik field (PEF) terhadap kualitas ekstrak cabe jamu (Piper retrofractum Vahl.) - Askur Rahman; Hamzah Fansuri; Banun Diyah Probowati; Agus Miftah Mutolip Sa’diyah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Piper retrofractum Vahl. have the potential to be developed into standardized medicinal ingredients. However, the extraction process of the active compounds in Piper retrofractum Vahl. needs further exploration to get the right method. This is necessary because previous studies state that conventional extraction requires a long time, while modern extraction technology has the disadvantage of being difficult to apply in society. Therefore the aim of this study was to obtain the PEF pre-treatment conditions in the extraction process which affected the quality of the Piper retrofractum Vahl. extract obtained. The stages in this study included the pre-treatment of Piper retrofractum Vahl. with PEF at a voltage (T1 = 5000, T2 = 5000, and T3=6000 volt) and an exposure time (W1=240 and W2=480 seconds), and was macerated using 96% ethanol solvent. The results of Piper retrofractum Vahl. extract with PEF pre-treatment produced a thick extract, dark brown color, characteristic odor, and spicy taste with a yield of 10.64±1.67%, water content 6.30±0.18%, total ash content 0.14±0.03%, acid insoluble ash content 0.25±0.01%, essential oil content 3.00±0.00% and piperine content of 40.38±2.44%.